Mass Shootings Anxiety Scale: A preliminary psychometric study. - Lee, Sherman Aclaracion (Death Studies, 2024)
Mass shootings have caused many to feel anxious and afraid of this seemingly common event. Therefore, the objective of this study was to develop and evaluate the properties of the Mass Shootings Anxiety Scale (MSAS), which is a five-item scale that was based on 759 adults. The MSAS demonstrated solid reliability (α and ω of 0.93), factorial validity (PCA and CFA support), and convergent validity (e.g., correlations with functional impairment and drug/alcohol coping). The MSAS also measures anxiety equivalently across gender, political orientation, and gun violence exposure groups. The MSAS not only discriminates well between persons with and without dysfunctional anxiety, using a cut score of ≥10 (92% sensitivity and 89% specificity), but also demonstrates incremental validity by explaining 5% to 16% additional variance in important outcomes beyond sociodemographics and posttraumatic stress. These preliminary results support the MSAS as a valid screening tool for clinical practice and scholarly inquiry.